INTRODUCTION OF THE BIOETHICAL IMPERATIVE IN MEDICAL EDUCATION AS A WY TO OPTIMIZING MODERN MEDICINE (Scientific journal of the Fergana State University, 2026)
Our era is characterized by progress in science and technology, innovation and discovery, including advances in medical and biological sciences. New biomedical technologies have fundamentally changed the image of medicine as a science and a field of activity, as their application has led to the emergence of unprecedented, controversial, and complex new problems. The potential of new biotechnologies has raised issues regarding medical ethics, patient rights, and their religious beliefs, faith, and personal values. These factors increase the need to find solutions to these problems through the bioethical imperative. In this article, the author focuses on the role of bioethics in optimizing medical education.